PENGARUH NILAI BAGI MAHASISWA DAN LINGKUNGAN INDIVIDU MAHASISWA TERHADAP PROSES PENGAMBILAN KEPUTUSAN DALAM MEMILIH PERGURUAN TINGGI - Yudhiantoro, Danang (Universitas Muhammadiyah Surakarta, 2007)
This research analyzes the effects of customer value to consumer decision inÂ education industry. Customer value is one of many factors, that give effect to choose productor service. Consumers will consider which product or service give the highest value forÂ them. This research analyzes the effect of customer value to consumer decision in the highÂ education industry. The result shows that value gives effect to consumer decision.